Faktor Penyebab Rendahnya Kesadaran Masyarakat Terhadap Pendidikan di Desa Mulyosari Kecamatan Pagerwojo Kabupaten Tulungagung - Ida Faridatul Maskhuroh; Mohammad Hasib (Arbain Publishing, 2025)
This research aims to analyze the factors contributing to the low public awareness of education in Mulyosari Village, Pagerwojo District, Tulungagung Regency. Employing a descriptive qualitative method, data was collected through in-depth interviews, observations, and documentation studies involving parents, school-aged children, and community leaders. The findings indicate that public awareness of education remains relatively low, despite a conceptual understanding of its importance. The primary contributing factors include limited family economic conditions , lack of intrinsic motivation from children to learn , insufficient parental support , the influence of peers and a social environment that prioritizes work , cultural stigma and gender stereotypes that deem education unimportant, especially for females , and the phenomenon of early marriage. Although the village government has made efforts such as providing assistance and conducting socialization , these complex obstacles necessitate a holistic and sustainable approach to change mindsets and increase educational participation in the village.